Conscientious Objections during COVID-19 Pandemic - Gupta, Deepak (Indian Journal of Community Health, 2020)
Globally evolving COVID-19 pandemic has raised major questions which may have catastrophic implications like absence of universal facemask use, misunderstanding implications of SARS-CoV-2 test results, ventilator related mortality, cytokine reduction technology and anti-viral treatments being in their infancy still, failure to update advanced healthcare directives during pandemic, and overlooked home hospice options for COVID-19 patients when terminally ill. Moreover, there are inquisitive and interesting avenues worth exploring and innovating during COVID19 pandemic like “cold” viruses such as SARS-CoV-2 uniquely choosing airways which normally and naturally have temperatures much lower than core body temperatures, potential therapeutic role (if any) of facemask usage, potential role of natural disinfection by sunlight and its component ultraviolet-C which is used for artificial cleansing, potential bimodal immune response against SARS-CoV-2, and exploration into BCG vaccination based non-specific protection against intracellular pathogens with SARS-CoV-2 itself being an intracellular pathogen. Summarily, I am praying that the natural delays in establishing reproducible evidence during COVID-19 pandemic should not turn the humanity as we know today into a historical evidence.